2013
DOI: 10.1002/ece3.851
|View full text |Cite
|
Sign up to set email alerts
|

Testing for intraspecific postzygotic isolation between cryptic lineages ofPseudacris crucifer

Abstract: Phenotypically cryptic lineages appear common in nature, yet little is known about the mechanisms that initiate and/or maintain barriers to gene flow, or how secondary contact between them might influence evolutionary trajectories. The consequences of such contact between diverging lineages depend on hybrid fitness, highlighting the potential for postzygotic isolating barriers to play a role in the origins of biological species. Previous research shows that two cryptic, deeply diverged intraspecific mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 121 publications
(219 reference statements)
1
8
0
Order By: Relevance
“…In the absence of quantified fitness consequences in hybrid P. crucifer (Stewart and Lougheed, 2013), plausible alternatives for the patterns that we observed require discussion. For example, asymmetrical mtDNA introgression may be caused by local adaptation, mtDNA-nDNA coevolution or selective sweeps of universally favoured mutations (Irwin et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the absence of quantified fitness consequences in hybrid P. crucifer (Stewart and Lougheed, 2013), plausible alternatives for the patterns that we observed require discussion. For example, asymmetrical mtDNA introgression may be caused by local adaptation, mtDNA-nDNA coevolution or selective sweeps of universally favoured mutations (Irwin et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Hybrid males show gametic (Wang, 2012) and behavioural (alternative mating tactic) dysfunctions (Stewart, 2013), in addition to some observations of higher tadpole mortality in hybrids under stressful developmental periods (Stewart and Lougheed, 2013), although this latter finding requires confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to fertilization presumably arise late in the speciation process, with some authors positing that selection against gamete wastage should favour the evolution of earlier-acting reproductive barriers [ 51 ]. Premating isolation through both acoustic differences and population-specific female preference have indeed been shown in spring peepers [ 14 ], while postzygotic reproductive barriers, as demonstrated through experimental evidence on spring peeper tadpoles, remains incomplete [ 52 ]. Divergence in spring peeper external morphology is relatively cryptic and no one has yet suggested that these lineages be recognized as incipient species.…”
Section: Discussionmentioning
confidence: 99%
“…Female HE individuals are significantly smaller than their contact zone counterparts (Stewart et al ., ) and female size correlates with fecundity both within (Camargo et al ., ) and among (Prado & Haddad, ) anuran species. Further, preliminary research also suggests tadpole competitive inferiority for HE individuals causing high levels of juvenile mortality (Stewart & Lougheed, ). Taken together, a decrease in HE fecundity and an increase in HE mortality may help to explain a decrease in proportions of Eastern hybrids within the contact zone.…”
Section: Discussionmentioning
confidence: 99%